The isolation and partial characterisation of the chalcone synthase, flavanone 3-hydroxylase and phytoene synthase gene fragments from oncidium taka by using RT-PCR - Ong, Wai Kean (2000)
The RT-PCR technique was used to isolate partial gene fragments for the chalcone synthase (CRS), flavanone 3-hydroxylase (F3H) and phytoene synthase (PSY) genes from 0. taka. The RT-PCR products were amplified by degenerate primers specifically designed for the genes and the templates (total RNA) were prepared from the leaves, open flowers and flower buds of 0. taka. A 6S0bp RT -PCR product was successfully amplified from the three different total RNA templates when the degenerate primers for CHS were used. Similarly, a 543bp RT-PCR product was obtained when the degenerate primers for PSY were used on the three different total RNA templates. Only the total RNA preparation from flower buds gave a 503bp RTPCR product when the degenerate primers for F3H were used. The deduced amino acid sequence for the 650bp DNA fragment was found to have a high homology to other CHS sequences in the Genebank, averaging at 66%. Additionally, this sequence also has an exceptionally high homology to previously reported bibenzyl synthase (BibSyl) sequences, with an average percentage of 85%. The 503bp fragment has on average 76% homology to the F3H sequences reported for other plant species. As for the 543bp fragment, it has an avemge of 76% homology to other PSY gene sequences published at Genebank. The results indicate that the CHS and PS Y genes are expressed in all the tissues tested whereas the F3 H gene is only expressed at the flower bud stage in 0. taka. These gene fragments were labelled with DIG and used as probes to screen a genomic DNA library constructed from partially digested genomic DNA of O. taka. Currently, the F3H probe (503bp DNA fragment) has led to the isolation of a genomic clone with an insert size of around 11kb. The genomic clone was restricted into 2 fragments with BamH I and subcloned into the pUC 18 vector separately. The characterisation of the clone is underway.